2019
DOI: 10.1098/rstb.2019.0066
|View full text |Cite
|
Sign up to set email alerts
|

The legacy of larval infection on immunological dynamics over metamorphosis

Abstract: Insect metamorphosis promotes the exploration of different ecological niches, as well as exposure to different parasites, across life stages. Adaptation should favour immune responses that are tailored to specific microbial threats, with the potential for metamorphosis to decouple the underlying genetic or physiological basis of immune responses in each stage. However, we do not have a good understanding of how early-life exposure to parasites influences immune responses in subsequent life stages. Is there a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 60 publications
(81 reference statements)
2
38
0
Order By: Relevance
“…It is also possible that sensitivity is driven by spatial considerations, for example the rate of bacterial dissemination throughout the haemocoel, but it is not clear why this would differ among species and populations. Finally, these experiments compare inducible immune parameters among populations within the larval life stage, but whether the observed patterns remain consistent across host ontogeny (Critchlow, Norris, & Tate, ), or among males and females (Khan, Prakash, & Agashe, ), remains an avenue for future study. Uncovering the mechanism(s) regulating inducible sensitivity to microbe density, coupled with experimental evolution of sensitivity, would allow the estimation of the relative costs and benefits of microbe density‐dependent and independent inducible immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that sensitivity is driven by spatial considerations, for example the rate of bacterial dissemination throughout the haemocoel, but it is not clear why this would differ among species and populations. Finally, these experiments compare inducible immune parameters among populations within the larval life stage, but whether the observed patterns remain consistent across host ontogeny (Critchlow, Norris, & Tate, ), or among males and females (Khan, Prakash, & Agashe, ), remains an avenue for future study. Uncovering the mechanism(s) regulating inducible sensitivity to microbe density, coupled with experimental evolution of sensitivity, would allow the estimation of the relative costs and benefits of microbe density‐dependent and independent inducible immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that sensitivity is driven by spatial considerations, for example the rate of bacterial dissemination throughout the haemocoel, but it is not clear why this would differ among species and populations. Finally, these experiments compare inducible immune parameters among populations within the larval life stage, but whether the observed patterns remain consistent across host ontogeny (Critchlow, Norris, & Tate, 2019), or among males and females (Khan, Prakash, & Agashe, 2016),…”
Section: Future Directionsmentioning
confidence: 99%
“…while exhibiting pathogenic behavior towards others [57,58]. With respect to the latter, mature plants are often susceptible to different pathogens than developing plants [59,60,61,62]. We capture virus pathogenic behavior in VIDO in steps.…”
Section: The Virus Infectious Disease Ontologymentioning
confidence: 99%
“…Collectively, previous research on infection susceptibility and immunity in holometabolous insects defies neat conclusions about relative immune investment across ontogeny. In honeybee workers ( Apis mellifera ), for example, the activity of the melanization enzyme phenoloxidase increases steadily over development from larva to adult [11], while in the tobacco hornworm ( Manduca sexta ), melanization activity peaks in the larval stage and declines thereafter [12] (see [13] for further examples). Most studies, however, employ insect populations reared in (and evolving under) lab conditions, sometimes for substantial periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…To address this question, we turned to wild and lab-derived populations of flour beetles ( Tribolium castaneum and T. confusum ). Previous research in lab-reared T. castaneum has suggested that the regulation of immune [13] and cuticular [14] gene expression differs among life stages in uninfected individuals, while, in larvae specifically, different populations of both species exhibit natural variation in immune gene expression and resistance to bacterial infection [15]. To test whether immune gene expression and infection resistance in these populations differs among life stages, we injected larvae and adults from seven populations (four T. castaneum , three T. confusum ) with one of four increasing doses of the entomopathogenic bacterium Bacillus thuringiensis (Bt) or sterile media as a wounding control.…”
Section: Introductionmentioning
confidence: 99%